Land use, environment, and development experiences from the Chittagong Hill Tracts of Bangladesh - Rasul, Golam (A.H. Development Pub. House ; Distributor in India, Paragon Enterprise, 2009)
Study focused on Chittagong Hill Tracts, Region, Bangladesh.